2019
DOI: 10.1177/0706743719856851
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and Self-Harm in Recent Immigrants in Ontario, Canada: A Population-Based Study

Abstract: Objective: To estimate the rates of suicide and self-harm among recent immigrants and to determine which immigrant-specific risk factors are associated with these outcomes. Methods: Population-based cohort study using linked health administrative data sets (2003 to 2017) in Ontario, Canada which included adults ≥18 years, living in Ontario ( N = 9,055,079). The main exposure was immigrant status (long-term resident vs. recent immigrant). Immigrant-specific exposures included visa class and country of origin. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 51 publications
(68 reference statements)
3
23
0
Order By: Relevance
“…Detailed information including immigration class and landing date with systematic and uniform data collection distinguishes this study from other small homicide registry studies28 or other population-based immigrant homicide studies that lacked detailed immigration data 27 28. Results of our study are likely generalisable to other countries with a similarly large and heterogeneous immigrant population (eg, UK, Australia) 3139. Given that there is evidence to suggest deaths of undetermined intent may include a proportion of homicides,25 26 a sensitivity analysis was undertaken and found that the socioeconomic gradient of deaths of unknown intent were similar to homicide.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Detailed information including immigration class and landing date with systematic and uniform data collection distinguishes this study from other small homicide registry studies28 or other population-based immigrant homicide studies that lacked detailed immigration data 27 28. Results of our study are likely generalisable to other countries with a similarly large and heterogeneous immigrant population (eg, UK, Australia) 3139. Given that there is evidence to suggest deaths of undetermined intent may include a proportion of homicides,25 26 a sensitivity analysis was undertaken and found that the socioeconomic gradient of deaths of unknown intent were similar to homicide.…”
Section: Discussionmentioning
confidence: 85%
“…This research also highlights the need to recognise contextual factors such as immigration characteristics (ie, refugee status, time since immigration) as important for understanding the heterogeneity of immigrants as a whole and their risk for homicide victimisation more broadly. 31 Despite the immigrant health advantage, research shows that immigrant populations are over-represented in low-income groups, relative to non-immigrants 32 with many facing barriers in access to health services, unemployment and housing instability. 33…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Long-term male residents, those middle-aged or older and/or living in neighborhoods with low income levels had increased risk of suicide. 51 Targeted suicide prevention strategies were recommended for established immigrants. 46…”
Section: Resultsmentioning
confidence: 99%
“…Across these marginalized men, suicidality was linked to social isolation (immigration, homelessness, incarceration experiences) compounded by complex personal histories comprising traumas, 47,49,53 psychological despair, 54 and lack of access to resources. 50 52,54…”
Section: Resultsmentioning
confidence: 99%